Chemical Analysis of the Drug Mefenamic Acid in Herbal Medicine for Aches and Pains Komplit Sidomuncul UV-VIS Spectrophotometric Method - Arfinda Hanung Saputri; Bagus Made Virdiansyah; Habibah Inas Maulina (DAS Institute, 2023)
Jamu is a traditional medicine that is widely used by the community to prevent or help cure various diseases. There are many traditional medicines in Indonesia that do not contain chemicals. The mixing of BKO in herbal medicine is prohibited by the Indonesian government. Medicinal chemicals are medicinal chemical compounds that are intentionally added to herbal medicines with the aim of achieving the desired effect faster than usual. The medicinal chemical that is often added to jamu pegal linu is mefenamat acid. The purpose of this study is to analyze the BKO contained in jamu pegal linu